Genetic blueprinting of novel and performance traits-related SNPs in Indian Gir cattle using latest reference assembly : ddRAD analysis of Gir cattle for SNP discovery - Nidhi Sukhija; Anjali Choudhary; Kanaka KK; Jaglan, Komal; M Joel Devadasan; Jayakumar Sivalingam; Archana Verma (Indian Journal of Dairy Science, 2024)
Among the indicine breeds of cattle, Gir breed thrives in challenging arid habitats, produce more milk with less feed intake and are resistant to tropical diseases. Identification of novel and bias free SNPs are important to include in genetic studies and breeding programs. The current study aimed to explore SNPs in Gir cattle genome followed by annotation of the SNPs to different performance traits. Double-digest restriction site associated DNA sequencing (ddRAD-seq) was done and different bioinformatic tools and software used to mine SNPs and subsequent annotation to different performance traits. A total of 53,243 high quality SNPs were identified using the latest ARS-UCD 1.3 reference genome (GCF_002263795.2). In all, 2,931 SNPs were annotated to 452 candidate genes related to nine different traits of interest such as, milk production, reproduction, adaptation, disease-resistance, growth, carcass, coat thickness, coat colour, and domestication traits. ddRAD-seq offers mining of ascertainment free SNPs in a cost-effective way and hence the SNPs obtained in this studied population can be successfully used for population genetic studies and in breeding programs. The information mined in this study will aid in genetic improvement, designing appropriate breed improvement programmes and leveraging conservation efforts.